Traditional Ecological Knowledge in Indigenous Hunting Body Cultural Research as an Emerging Collaborative Self-Governing Approach for Green Ethical Cultural Advocacy as “Protected Belief Status” - Wei-Ta Fang; Toby Precious T. Nwachukwu; Nikky Lin; Chien-Shing Lee (SAGE Open)
The gaps in the literature and the nonexistence of restrictions from present-day legislation are the bane of Traditional Ecological Knowledge (TEK) in hunting cultural practice. This research explores and engages qualitative research by applying visual and dictated information on hunting body culture transformation for indigenous ecological knowledge. Ethical and greening advocacy an emerging collaborative framework for hunting activities through the eyes and experience of the aboriginal people of Taiwan was used to explore the relationships between TEK and self-governing management to grasp and experience the meaning of Hunting Body Culture (HBC). Twelve activities of Taiwan’s Gaga aboriginal hunting behaviors from longitudinal research from 2012 to 2024 were observed by reading hunting photo-voice information and interviewing fourteen aboriginal hunters. The findings include the utilization of Green Ethical Cultural Advocacy (GECA) to reflect the study’s outcomes on social norms, hunting harvest patterns, hunting ritual events, forming of hunting groups, the choice of hunting tools, game selection differences, personalized attributes like solitude; and generic tolerance for indigenous cultural heritage as a Protected belief transforming toward a legislative Protected Status . Future research should triangulate positivist/interpretive and mixed approaches to navigate the ethical justice pattern for TEK and the use of digital technology to administer greening ethical cultural advocacy in hunting. The implications of the research to theory and practice were specified, as we proposed four distinctive principles for green hunting.